Upaya Mereduksi Kebiasaan Bermain Game Online Melalui Teknik Diskusi Kelompok - Fauziawati, Wieke (Universitas Ahmad Dahlan, 2015)
The purpose of this study is an attempt to reduce the excessive habit of playing online games through group discussion techniques for 8th grade students of class D in SMP Muhammadiyah 3 Yogyakarta in the academic year 2013/2014. This study is an action research. The participants were 10 students selected using purposive sampling techniques. The instruments used are questionnaires of playing online games habit and observation. The analysis used in this research is the t-test formula. The treatment using group discussion techniques was given to the students after the guidance and counseling services were done. The results of this study showed that the average pretest percentage of the habit of playing online games is 90,9%, while the average posttest results is 57,6%. The results showed that there is a reduction of playing online games habit through group dicussion techniques for 8th grade students of class D in SMP Muhammadiyah 3 Yogyakarta. This study can be used as a basis information for guidance and counseling teachers in lessening the habit of playing online games through group discussion techniques.